Review on the conceptual framework of teacher resilience - Zhang, Shen; Luo, Yuzhou (Frontiers in Psychology, 2023)
Resilience is the ability to bounce back from setbacks and adapt to new circumstances. Resilient teachers can handle these issues. In this case, it’s proposed to interpret the recent decade’s resilience research on teachers. Provide a conceptual framework for teacher resilience factors. The Scopus database was used to collect articles. The titles and abstracts of articles were read one by one. As a result, 22 articles were included in the data analysis. The country where the data were collected, the aims of the study, the education level which the participants working, the sample size, the scale used, and the variables included in the study are marked in the full text. Most studies were effect determination, correlation, or exploratory. Initially, age and gender inequalities among instructors were examined. Postgraduate instructors are more resilient than undergraduates. Psychological factors, workplace variables, and teacher competency and attributes are used to study teacher resilience. Teachers’ resilience negatively impacts depression, stress, anxiety, well-being, and mood. Quality of life and well-being are positively connected. Job crafting, work engagement, and working environment are favorably connected, whereas job burnout and turnover intention are adversely correlated. Resilience was positively connected with emotion regulation, empathy, others’ emotion evaluation, teacher competence, teacher self-efficacy, and self-esteem in teachers. Anger, anxiety, mindfulness, pleasure, social support, fear, and training affect teachers’ resilience. Teachers’ resilience affects stress, depersonalization, personal accomplishment, emotional exhaustion, children’s resilience, job engagement, happiness, well-being, self-care, and success.